Influence of effective medium permeability on stability of a two-layer system "pure fluid-porous medium" under high-frequency vibrations - Kolchanova, Ekaterina Andreevna; Lyubimov, Dmitriy Victorovich; Lyubimova, Tatiana Petrovna (Computational Continuum Mechanics, 2012)
In the framework of the averaged approach a linear stability problem for a two-layer system consisting of pure fluid layer and porous medium saturated by the fluid under gravity and vertical high-frequency vibrations is investigated. It is shown that in the presence of vibrations neutral curves are bimodal in some range of parameters as in the case of a static gravity field. Vibrations stabilize the equilibrium of the two-layer system and increase the length of most unstable perturbation waves. Moreover, vibrations make long-wave perturbations to be most unstable at lower porous medium permeability and larger fluid layer thickness than in the absence of vibrations.